2018
DOI: 10.1016/j.pocean.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Origin of remineralized organic matter in sediments from the Rhone River prodelta (NW Mediterranean) traced by Δ 14 C and δ 13 C signatures of pore water DIC

Abstract: Rivers are important links between continents and oceans by transporting terrestrial particulate organic matter (POM) to continental shelf regions through estuaries or deltas and the Mediterranean basin is a good example of this strong linkage. In the vicinity of river mouths, an important fraction of the terrestrial POM settles on the seafloor, sometimes mixed with marine POM, where both can be recycled or buried. In the Rhone River prodelta, previous studies have investigated the origin of the POM in the sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 68 publications
(104 reference statements)
3
8
0
Order By: Relevance
“…The δ 13 C values around –25.5‰ calculated for the mineralized OM in the prodelta sediments (station A and Z) indicate strong mineralization of terrigenous sources whereas the calculated δ 13 C value around –20‰ at station D on the outer shelf indicates a marine source. These results are in accordance with Toussaint et al (2013) and the idea that most of the terrestrial OM is rapidly deposited and mineralized in the prodelta (Pozzato et al 2018) whereas further on the shelf less terrigenous substrate is deposited and it is mainly marine OM that is mineralized. In this zone, mineralization has a lower impact on the δ 13 C of pore waters DIC than in the prodelta with an isotopic composition strongly influenced by the seawater water bicarbonate (δ 13 C= –1‰).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The δ 13 C values around –25.5‰ calculated for the mineralized OM in the prodelta sediments (station A and Z) indicate strong mineralization of terrigenous sources whereas the calculated δ 13 C value around –20‰ at station D on the outer shelf indicates a marine source. These results are in accordance with Toussaint et al (2013) and the idea that most of the terrestrial OM is rapidly deposited and mineralized in the prodelta (Pozzato et al 2018) whereas further on the shelf less terrigenous substrate is deposited and it is mainly marine OM that is mineralized. In this zone, mineralization has a lower impact on the δ 13 C of pore waters DIC than in the prodelta with an isotopic composition strongly influenced by the seawater water bicarbonate (δ 13 C= –1‰).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the ∆ 14 C analysis of both sediment organic carbon and the corresponding pore waters DIC as well as bottom seawaters are reported in Figure 4. The ∆ 14 C signature of the bottom seawater was analyzed for station A (∆ 14 C=+39‰) and we assume that this value is the same for all three stations which is confirmed by Pozzato et al (2018), since, as shown above, the concentration of DIC is the same and the salinity of bottom waters is consistently around 38‰ at the three stations, suggesting that no mixing with fresh river water occurred.
Figure 4Results of 14 C analysis, expressed in ∆ 14 C (‰), at the three stations A, Z, and D and for two different kinds of samples: sediment pore waters DIC (symbols) and sediment organic carbon (crosses). Colors refer to stations.
…”
Section: Resultssupporting
confidence: 76%
“…At the proximal zone, the sedimentary OM deposition is characterised by terrestrial sources and aquatic PP, which is highly reactive. In contrast, at the shelf area, the major source of OM is marine PP (Pozzato et al, 2018). Here, slow settling through the water column allows longer exposure of OM to heterotrophic degradation prior to burial, resulting in an overall decrease in OM reactivity (e.g., Middelburg et al, 1997), whereas at shallow depths with great sedimentation rates the burial of reactive OM is favoured.…”
Section: Emerging Environmental Patterns In Om Reactivitymentioning
confidence: 99%
“…Finally, porewater DIC should have isotope signature similar to the organic matter source deposited to sediments (Aller et al 2008;Pozzato et al 2018) and its carbon signatures are highly variable because of methanogenesis (LaZerte 1981). Decomposed macrophytes and particulate organic matter are the main components of organic matter in lagoon sediments (Garzon-Garcia et al 2017), Because δ 13 C in macrophytes and particulate organic matter varies with salinity ( Figure 6), the δ 13 C-DIC in porewater is also likely to vary with salinity (thus a not-constant endmember), making it difficult to trace porewater δ 13 C-DIC in the lagoon waters.…”
Section: Contribution Of Different Nitrogen Sourcesmentioning
confidence: 99%